Erratum: High-throughput quantitation of inorganic nanoparticle biodistribution at the single-cell level using mass cytometry - Yu-Sang Sabrina Yang (Nature Portfolio, 2017)
Nature Communications 8 Article number: 14069 (2017); Published 17 January 2017; Updated 14 August 2017 In Fig. 4d of this Article, the schematic was incorrectly illustrated with one SIINFEKL peptide detached from a MUS/OT nanoparticle surface. The correct version of Fig. 4 appears below as Fig. 1.